Kolaborasi dan Peran Bank Sentral di Tengah Pandemic Covid-19 - Fuddin, Muhammad Khoirul; Soelistyo, Aris; Setyowati, Ika Yuli; Capridasari, Denita; Arista, Linda; Izzah, Evita Nurul (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
The purpose of this research is to find out what collaborations or collaborations have been carried out by the central bank in dealing with the Covid-19 pandemic that has occurred in recent years, including Bank Indonesia as the central bank in Indonesia. In this regard, we will also look at the role of the central bank in dealing with the Covid-19 pandemic. The research we conducted aims to examine scientific articles about the discussion of "Collaboration and the Role of the Central Bank in the Middle of the Covid-19 Pandemic". The role of the Central Bank when the Covid-19 pandemic surge occurred was to carry out QE policies carried out by the AE and EM Central Banks to maintain the function of the bond market so that it continued to operate properly, maintaining the availability of credit flowing to companies, and sustain monetary accommodation when the interest rate is at the practical lower bound point at the AE Central Bank. Bank Indonesia, as the state central bank of Indonesia, is also making efforts to reduce the risk of Covid-19, namely by implementing a policy mix through the National Economic Recovery (PEN) program, which is used to maintain the stability of the Rupiah exchange rate, the financial system, and to control inflation.